2007
DOI: 10.1021/bi7013294
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inhibition of Sir2 Deacetylases by Thioacetyl-Lysine Peptide

Abstract: Sir2 protein deacetylases (or sirtuins) catalyze NAD+-dependent conversion of epsilon-amino-acetylated lysine residues to deacetylated lysine, nicotinamide, and 2'-O-acetyl-ADP-ribose. Small-molecule modulation of sirtuin activity might treat age-associated diseases, such as type II diabetes, obesity, and neurodegenerative disorders. Here, we have evaluated the mechanisms of sirtuin inhibition of histone peptides containing thioacetyl or mono-, di-, and trifluoroacetyl groups at the epsilon-amino of lysine. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
155
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(163 citation statements)
references
References 33 publications
5
155
0
3
Order By: Relevance
“…Comparison between SIRT5-Bicyclic Intermediate and SIRT3-Alkylamidate Intermediate-Kinetic studies and mass spectrometry have demonstrated the existence of the alkylamidate and 1Ј,2Ј-cyclic intermediates (18,19 (21). When comparing the SIRT5-bicyclic intermediate structure with the SIRT3-alkylamidate intermediate structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison between SIRT5-Bicyclic Intermediate and SIRT3-Alkylamidate Intermediate-Kinetic studies and mass spectrometry have demonstrated the existence of the alkylamidate and 1Ј,2Ј-cyclic intermediates (18,19 (21). When comparing the SIRT5-bicyclic intermediate structure with the SIRT3-alkylamidate intermediate structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The absolutely conserved histidine residue among sirtuins serves as a general base to deprotonate the 2Ј-OH directly or indirectly through the deprotonation of the 3Ј-OH to attack the 1Ј-O-alkylamidate. Kinetic and mass spectrometry experiments suggested the existence of the alkylamidate and the bicyclic intermediates (18,19). Using a mechanism-based inhibitor (a thioacetyl-lysine peptide), the S-alkylamidate intermediate was captured in Sir2Tm and SIRT3 crystals (20,21).…”
mentioning
confidence: 99%
“…Utilization of acetyllysine analogs further demonstrated the existence of the alkylamidate intermediate. Thioacetyllysine-and acetylazalysinecontaining peptides form stalled alkylamidate intermediates when used as sirtuin substrates (19,20). Upon formation of the alkylamidate intermediate, the 2Ј-hydroxyl group of the NAD ϩ ribose is activated by a conserved active-site histidine (supplemental Fig.…”
Section: Unique Chemistrymentioning
confidence: 99%
“…Work in a variety of systems has shown that they play roles in many key cellular processes including gene regulation, aging, cell survival, metabolic control, and DNA repair (Brachmann et al 1995;Kaeberlein et al 1999;Lin et al 2000;Langley et al 2002). Small molecule inhibitors and activators of sirtuin activity have received considerable attention recently as potential therapeutic agents for aging-associated diseases including Parkinson's disease and type II diabetes (Smith and Denu 2007). Thus, there is substantial general interest in understanding how this family of enzymes is regulated.…”
mentioning
confidence: 99%